Import Dependence and Food and Nutrition Security Implications: The Case of Pulses in India. (April 2017) - Bhattacharjya, Souvik; Chaudhury, Saswata; Nanda, Nitya
Pulses are the staple sources of protein for Indians and contribute significantly to their nutritional security. However, limited growth in domestic production, has led to India's increased import dependence. India's import of pulses almost doubled in the last ten years and is currently estimated to be more than 3 million tonnes. Imports account for 15–20 per cent of total domestic production. The article presents the factors behind stagnating pulses production, India's vulnerability to pulses import shortage and thereby food security implications. It also suggests strategies to promote sustainable supply of pulses to ensure food security. JEL: Q130, Q180, Q170, Q020, F680